Efektivitas Komunikasi Pembelajaran Daring terhadap Pemahaman Materi Kuliah Mahasiswa UIN Sunan Ampel Surabaya - Rahmadani, Desy; Nurdin, Ali (Jurnal Ilmu Komunikasi, 2021)
This study discusses the effectiveness of online learning communication on the understanding of lecture material for UIN Sunan Ampel Surabaya students. This research method uses a quantitative approach with the type of correlational research. The data was collected using a questionnaire technique through the google form application, the sampling technique was carried out using a random sample technique, and analyzed using the Chi Square statistical formula and the Correlation Coefficient. The results showed that the calculation of the data using the Chi Square formula with the suitability of the table 0.05% resulted in x2 arithmetic > x2 table (60.69 > 3.84), so Ha was accepted while Ho was rejected. It can be concluded that there is an effectiveness of online learning communication on the understanding of lecture material for UIN Sunan Ampel Surabaya students. Then, to measure the level of effectiveness, the researcher used the correlation coefficient formula and obtained a value of 0.134 with a very low category.